1975
DOI: 10.1111/j.1365-2818.1975.tb04024.x
|View full text |Cite
|
Sign up to set email alerts
|

The myofibrillar M‐band in the cryo‐section—analysis of section thickness

Abstract: SUMMARY Information regarding the formation and the thickness of cryo‐sections is of importance for an adequate interpretation of cryo‐sectioned biological material. In this study we have taken advantage of the regular arrangement of filaments in myofibrils in an analysis of these matters. It is concluded that the sections are formed partly by fracturing in a way similar to that visualized in replicas made by the freeze‐fracturing and ‐etching procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In electron micrographs of striated muscle, the M-line appears to be made up of several transverse elements connecting the thick filaments through the bare zone region and gives rise to the typical hexagonal thick filament lattice (Franzini-Armstrong and Porter 1964). Ultrathin frozen sections of muscle show up to nine symmetrically arranged transverse elements (M1-M9 and M1′-M9′) in each half of the M-line structure (Thornell and Sjöström 1975; Sjöström and Squire 1977; Carlsson et al 1990). Immunoelectron microscopic data suggest that MM-CK is part or associated with the prominent M4 and M4′ cross-bridges, also visible by conventional electron microscopy (Wallimann et al 1983a; Wallimann and Eppenberger 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In electron micrographs of striated muscle, the M-line appears to be made up of several transverse elements connecting the thick filaments through the bare zone region and gives rise to the typical hexagonal thick filament lattice (Franzini-Armstrong and Porter 1964). Ultrathin frozen sections of muscle show up to nine symmetrically arranged transverse elements (M1-M9 and M1′-M9′) in each half of the M-line structure (Thornell and Sjöström 1975; Sjöström and Squire 1977; Carlsson et al 1990). Immunoelectron microscopic data suggest that MM-CK is part or associated with the prominent M4 and M4′ cross-bridges, also visible by conventional electron microscopy (Wallimann et al 1983a; Wallimann and Eppenberger 1985).…”
Section: Discussionmentioning
confidence: 99%
“…). In parallel, it became evident that in negatively stained ultrathin cryosections, the M‐band had distinct lines/striations crosslinking the thick filaments, forming M‐bridges and M‐filaments (Thornell & Sjöström, ). Interestingly, the lines showed a fibre type‐related appearance in human limb skeletal muscle of 3, 3 + 2 or 5 lines (Sjostrom & Squire, ; Fig.…”
Section: Fibre Typing On Basis Of Ultrastructural Variability In M‐bamentioning
confidence: 99%
“…High resolution electron microscopy using ultrathin cryosections showed that the M-line is actually composed of substriations, with the number of striations varying among different muscle types (32,33). Three structural elements have been identified: primary and secondary (Y-shaped) M-bridges and M-filaments (14,16,20,27,33,39) . Only vague notions exist on the function of this complex structure running across the sarcomere at the height ofthe bare zone of thick myosin filaments (6,10,21).…”
mentioning
confidence: 99%